Religious education in Poland: between absence and presence - Hejwosz-Gromkowska, Daria (EDUsfera. Ewa Jurczyk-Romanowska, 2020)
The nature of religious education or religious instruction may vary in different societies. The confessional religious education, namely catechesis, dominates in public schools, as the Roman Catholic Church continues to hold a strong position in Poland. Considering the fact that 94.2% of elementary school students receive the catechism, the author of the paper was interested in whether the Polish elementary schools teach about different religions, religious diversity, and religion as a cultural phenomenon?
Keywords: religious education; Poland; catechesis; National Curriculum; elementary school